2023
DOI: 10.1001/jamasurg.2022.5674
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture vs Sham Electroacupuncture in the Treatment of Postoperative Ileus After Laparoscopic Surgery for Colorectal Cancer

Abstract: ImportanceDespite the adoption of the optimized Enhanced Recovery After Surgery (ERAS) protocol, postoperative ileus (POI) severely impairs recovery after colorectal resection and increases the burden on the health care system.ObjectiveTo assess the efficacy of electroacupuncture (EA) in reducing the duration of POI with the ERAS protocol.Design, Setting, and ParticipantsThis multicenter, randomized, sham-controlled trial was conducted in China from October 12, 2020, through October 17, 2021. There was a 1:1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
49
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 41 publications
1
49
0
Order By: Relevance
“…In patients undergoing laparoscopic surgery, the time to defecation was shortened as well. 20 However, whether the potential benefit of TEAS on gastrointestinal function could shorten the length of stay after surgery is not clear. Therefore, the aim of this multicenter randomized trial was to evaluate whether perioperative TEAS could further improve the gastrointestinal function and shorten the time to meet the discharge criteria in patients undergoing laparoscopic colon surgery with current ERAS approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In patients undergoing laparoscopic surgery, the time to defecation was shortened as well. 20 However, whether the potential benefit of TEAS on gastrointestinal function could shorten the length of stay after surgery is not clear. Therefore, the aim of this multicenter randomized trial was to evaluate whether perioperative TEAS could further improve the gastrointestinal function and shorten the time to meet the discharge criteria in patients undergoing laparoscopic colon surgery with current ERAS approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Still, delayed gastrointestinal function prolongs hospital stay in well-functioning ERAS settings. 2 In JAMA Surgery, Wang et al 3 present data suggesting that the use of electroacupuncture could be an additional element to consider in the multimodal approach to speed up the return of gut motility and function after colorectal surgery.…”
mentioning
confidence: 99%
“…In their randomized clinical trial, Wang and colleagues found a reduction of the duration of postoperative ileus and 50% decreased risk of prolonged postoperative ileus in patients treated with electroacupuncture compared with sham electroacupuncture. This holds interest because the mode of action, although not fully clear, is likely different from other treatments for this condition and could be complementary in the multimodal approach.…”
mentioning
confidence: 99%
“…To the Editor We read with great interest the Original Investigation by Wang et al 1 focusing on the efficacy of electroacupuncture (EA) treatment for postoperative ileus (POI) after laparoscopic colorectal cancer (CRC) resection. They concluded that EA contributed to a shortened duration of POI and reduced risk for prolonged POI compared with sham electroacupuncture (SA).…”
mentioning
confidence: 99%